The Role of Small Bowel Capsule Endoscopy in Determining the Treatment Strategy for Duodenal Follicular Lymphoma: A Single-Center Retrospective Study - Donghoon Kang; Gi-June Min; Tong Yoon Kim; Young-Woo Jeon; Yukyung Cho; Jae Myung Park; Joo Hyun O; Byung-Ock Choi; Gyeongsin Park; Seok-Goo Cho (Diagnostics)
Objectives: In this single-center retrospective study, we aimed to verify the extent of duodenal follicular lymphoma (DFL) and investigate the role and clinical significance of video capsule endoscopy (VCE) in the treatment process. Methods: We analyzed the clinical and imaging data of 40 patients diagnosed with DFL. Results: Imaging workup and bone marrow biopsies revealed DFL only in the gastrointestinal tract (stage I) in 22 patients and in local lymph nodes (stage II1), distant lymph nodes (stage II2), pancreas (stage II2Epancreas), and extranodal regions (stage IV) in 1, 3, 1, and 13 patients, respectively. Fifteen of the 23 patients with localized (stages I and II1) DFL underwent VCE for comprehensive small bowel evaluation, which revealed lesion extension beyond the duodenum in 10 patients (66.7%). A watch-and-wait strategy was implemented for one patient and systemic chemotherapy was administered to the remaining nine. Of the eight patients without VCE, seven and one received radiotherapy and observation, respectively. Nine of the 23 patients (39.1%) received systemic treatment based on positive VCE results. Only one of the 17 patients with advanced-stage DFL (stages II2 and IV) accepted radiotherapy; 16 underwent systemic chemotherapy. During follow-up (median, 48.4 months), two relapse events occurred in the advanced stage, with no lymphoma-associated deaths. DFL tends to be indolent and has favorable outcomes. Conclusions: Proactive VCE for diagnosing DFL is recommended to determine small bowel involvement, which may influence subsequent treatment decisions.